Policing major events: perspectives from around the world - Albrecht, James F.; Dow, Martha C.; Plecas, Darryl; Das, Dilip K. (International Police Executive Symposium co-publications, 2015)
"Whenever a major event requires police intervention, questions are raised about the nature of the police response. Could the police have prevented the conflict, been better prepared, reacted more quickly? Could they have acted more forcefully or brought the altercation under control more effectively? Based upon real case studies of events from all over the world, this volume explores the complex set of factors comprising the policing of major events. Topics covered include:Police procedures in Serbia in response to sporting events and violenceThe 2010 World Cup in South Africa as a model of best practice in governance structures, along with the region's struggles in routine policing initiativesSecurity operations at the 2010 Winter Olympic Games in Canada and the Summer Olympic and Paralympic Games in London in 2012Community involvement to curb terrorist insurgency in North Eastern NigeriaGovernmental response to Hurricane Katrina in Louisiana and TexasRevisions made to NYPD protocols following the September 11 attacksPolicing strategies for major events on Aboriginal and tribal lands across CanadaOther topics include the police/protestor relationship and low-profile versus high-profile policing strategies in crowd control, the growing strategy of private security in working with public police forces, and enhancing public safety in post-conflict regions. The concepts presented in Policing Major Events: Perspectives from Around the World will enable police departments to improve their readiness for policing major events across a diverse set of events and socio-political contexts. This book is a co-publication with the International Police Executive Symposium. "--